Malignant spinal cord compression: an emergency in oncology - Sofia Lopes Simões, Ângela (2011)
Malignant spinal cord compression is a serious and frequent emergency in oncology which requires prompt diagnosis and treatment for pain relief and preservation of neurological function.The effects of spinal cord compression are demonstrated by sensory, motor and autonomous minima changes to episodes of severe pain or, in severe cases, complete paralysis that definitely affects the quality of life of patients.Failure in the correct diagnosis in conjunction with a limited knowledge of appropriate referral for immediate treatment results in a complete paralysis and in most cases irreversible, since 90% of ambulatory patients may remain ambulatory if we act promptly. Without therapy, the malignant spinal cord compression is a significant source of morbidity and mortality, severe pain, paralysis, incontinence and a decreased quality of life.